2019
DOI: 10.17724/jicna.2019.162
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of children with epilepsy managed at an urban hospital in Africa: a retrospective study

Abstract: Background Most children with epilepsy reside in resource-limited regions such as sub-Saharan Africa, where the majority of studies have been conducted in rural areas with limited investigations. Medical records from children with epilepsy seen at an urban hospital in Kenya were examined to provide a comprehensive description of epilepsy in children from this hospital.   Methods A retrospective observational study was conducted which involved reviewing medical records of 426 epilepsy pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
2
1
1
Order By: Relevance
“…Epileptic seizures were found to be more common in males (60.9%) than in females (39.1%). This is in line with a study done in Kenya [ 25 ]. Less than half of the patients (40.2%) belonged to the age group 10 to 15 years.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Epileptic seizures were found to be more common in males (60.9%) than in females (39.1%). This is in line with a study done in Kenya [ 25 ]. Less than half of the patients (40.2%) belonged to the age group 10 to 15 years.…”
Section: Discussionsupporting
confidence: 93%
“…Less than half of the patients (40.2%) belonged to the age group 10 to 15 years. This is different from the other studies carried out in Malaysia, Kenya and India in which a majority of children fall in the age group of 6 to 10 year [ 14 , 25 , 26 ].…”
Section: Discussioncontrasting
confidence: 84%
“…In this study, it was found that 53.5% of children reporting epilepsy were male. This is in accordance with the data from another developing African country where 61.0% of children with epilepsy coming to a pediatric neurology clinic were male [14]. As in this study, the majority of the children (62.8%) children belonged to rural areas of residence [14]; cultural and social beliefs might be the reason behind this male predominance among children with epilepsy who are brought to healthcare centers for treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Access to neuroimaging (MRI and CT scans) and neurophysiological testing [electroencephalography (EEG)] is typically concentrated in large urban centers in SSA (11,12). Accordingly, there are few studies that have provided a description of imaging findings in children with epilepsy in SSA.…”
Section: Discussionmentioning
confidence: 99%